Airborne mould spores of allergenic importance - Th.M. Spieksma, Frits (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
The author described highly allergenic mould spores which may be classified as indoor and outdoor. 10 most common mould spores being detected in Europe were presented. Some distinct differences between outdoor and indoor species of various regions in Europe were noted and discussed in European research literature.